PENGARUH DOSIS TRICHOKOMPOS PUPUK KANDANG KOTORAN SAPI DAN PUPUK UREA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SAWI SAMHONG (Brassica juncea L.) - Kelen, Oswaldus Emanuel R.; Kasim, Muhamad; Nguru, Elias St. O. (JURNAL AGRISA, 2024)
This research was conducted at the UPT Land: Archipelago Dry Land Laboratory, Nusa Cendana University, Kupang from February to May 2024. The purpose of this research was to determine the interaction effect of trichocompost fertilizer dose and urea fertilizer dose on the growth and yield of Samhong mustard greens (Brassica juncea L.) and to determine the treatment of trichocompost fertilizer dose and urea fertilizer dose that provides the best growth and yield of Samhong mustard greens (Brassica juncea L.). This research was designed using a Factorial Randomized Group Design (RAK) consisting of two factors, the first factor is the dose factor of trichocompost fertilizer which consists of three treatment levels, namely 0, 90 g/plant, and 180g/plant. The second factor is the urea fertilizer dosage factor with five treatment levels, namely 0; 0.6 g/plant; 1.2 g/plant; 1.8 g/plant; and 2.4 g/plant. As a result, 15 treatment combinations were made in three groups, totaling 45 experimental units. Each experimental unit consisted of 24 plants and 8 plants were used as sample plants, so there were 1080 plants. The results showed that the interaction of trichocompost fertilizer dose treatment had a real effect on the observation variables of plant height, gross wet fresh weight per plot, and net wet fresh weight per plot. The dose of trichocompost fertilizer 180 g/plant and the dose of urea fertilizer 1.2 g/plant gave the best effect on plant height increase of 19.88 cm/30 days after transplanting (DAT). The dose of trichocompost fertilizer 180 g/plant and the dose of urea fertilizer 2.4 g/plant gave the best effect on gross wet fresh weight of 6250.67 g/1,44 m2 and net wet fresh weight of 5570.67 g/1,44 m2